Transformations of urban space, place and non-place - Gaweł, Dariusz (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
The paper is a continuation of research on urban space in conditions of universal globalization. It was created based on the criticism of professional literature as well as observations and research "in situ" relating to the places described. The term "non-place" is the basis for an assessment of urban space in the conditions of rapidly changing changes in the built environment of cities and its users. Changing living conditions, technological progress and computerization of processes impose many additional challenges on the inhabitants. While historically shaped urban structures have naturally developed features of the identity of a place, rapidly emerging non-places show a complete lack of them. Contemporary non-places become the meeting point of the created architecture, urban planning and the negative effects of the social life of the inhabitants. They are created in apparent conditions of concern for the common good, contemporary cities slowly become pauperized. The paper is a confrontation of theoretical considerations supported by the analysis of specific implementations.